School social work in northern Uganda in a post-conflict context: A case of Anaka Foundation - Julius Omona (International Journal of School Social Work, 2018)
Anaka Foundation is an indigenous NGO that is operating in northern Uganda in response to the post-war development challenges. Anaka recently concluded a school social work project, a specialization which is common in Western countries, to attempt to improve the learning environment of vulnerable children selected from nine government aided primary schools. This school social work pilot project was supported with a grant from AfriCarinthia, an organization from Austria. Relevant social work theories were applied and significant systems in the learning environment of the children were targeted through different interventions. A mixed before-and-after evaluation approach was used to arrive at comparison of outcomes. The findings, amongst others, indicate that school social work had a significant positive impact on the children and the key systems involved. There were improvements in educational quality, access, and engagement; and thus should be pursued by the Uganda government, and indeed by other developing countries attempting to improve the education services to their citizens.
Keywords: School social work; civil society; post-conflict; children; education